2019
DOI: 10.3390/app9091892
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Solution for Broadband PLC Splitter with Variable Splitting Ratio Based on Asymmetric Three Waveguide Structures

Abstract: A numerical solution for the broadband planar-lightwave-circuit (PLC) splitter with a variable splitting ratio based on asymmetric three waveguides weighted by the Blackman weighting function is designed for passive optical network applications with wavelengths between 1.53 and 1.57 µm. The performance of the proposed splitter is verified using the beam propagation method (BPM). It was found that a polynomial function of the splitting ratios accompanying a geometrical shift can be derived from the proposed spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The first paper by Boucouvalas, et al [22] is a review of the resonant transmission line method, which enables the design of elliptical and eccentric core fibers as well as "holey" photonic crystal fibers. Wang, et al [23] have presented a broadband planar lightwave circuit splitter with a variable splitting ratio that is designed for signal distribution in passive optical network. Li, et al [24] have reported pulse-shaping-based optical transmission for a 128-QAM (quadrature amplitude modulation) DWDM (dense wavelength division multiplexing) system that has a potential capacity equal to 904 Gbps per channel.…”
Section: Components and Networkmentioning
confidence: 99%
“…The first paper by Boucouvalas, et al [22] is a review of the resonant transmission line method, which enables the design of elliptical and eccentric core fibers as well as "holey" photonic crystal fibers. Wang, et al [23] have presented a broadband planar lightwave circuit splitter with a variable splitting ratio that is designed for signal distribution in passive optical network. Li, et al [24] have reported pulse-shaping-based optical transmission for a 128-QAM (quadrature amplitude modulation) DWDM (dense wavelength division multiplexing) system that has a potential capacity equal to 904 Gbps per channel.…”
Section: Components and Networkmentioning
confidence: 99%
“…Although the uniform OPS has been researched comprehensively and well-thought-out, non-uniform OPS, or tunable OPS is needed in some specific application scenarios which require unequal power splitting ratio (PSR), such as: power equalizers [7], ring lasers [8], [9], optical switch [10] and modulators [11]. The proposed schemes of tunable OPS can be divided into three classes: direction coupler (DC) [12], [13], Y junction [14], [15] and multimode interference coupler (MMI) [16], [17]. Two schemes based on DC structure have been proposed in [12] and [13].…”
Section: Introductionmentioning
confidence: 99%
“…The proposed schemes of tunable OPS can be divided into three classes: direction coupler (DC) [12], [13], Y junction [14], [15] and multimode interference coupler (MMI) [16], [17]. Two schemes based on DC structure have been proposed in [12] and [13]. By adjusting the gaps between the middle waveguide and the two parallel outer waveguides in [12], the PSR of the OPS can vary from −9.55 dB to 9.55 dB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation